Corruption, global security, and world order - Rotberg, Robert I.; American Academy of Arts and Sciences. Committee on International Security Studies; John F. Kennedy School of Government. Program on Intrastate Conflict; World Peace Foundation (Cambridge, Mass. : World Peace Foundation : Harvard Kennedy School Program on Intrastate Conflict : American Academy of Arts & Sciences ; Washington, D.C. : Brookings Institution Press, 2009)
"Discusses global ramifications of deeply embedded corruption by criminals and criminalized states. Explores trafficking issues--how nuclear/WMD smugglers coexist with other traffickers. Examines how corruption deprives citizens of fundamental human rights, assesses the connection between corruption and the spread of terror, and proposes remedies to reduce and contain corruption"--Provided by publisher.
Preface -- 1. How corruption compromises world peace and stability / Robert I. Rotberg -- 2. Defining corruption : implications for action / Laura S. Underkuffler -- 3. Defining and measuring corruption : where have we come from, where are we now, and what matters for the future? / Nathaniel Heller -- 4. Corruption in the wake of domestic national conflict / Susan Rose-Ackerman -- 5. Kleptocratic interdependence : trafficking, corruption, and the marriage of politics and illicit profits / Kelly M. Greenhill -- 6. Corruption and nuclear proliferation / Matthew Bunn -- 7. To bribe or to bomb : do corruption and terrorism go together? / Jessica C. Teets and Erica Chenoweth -- 8. Corruption, the criminalized state, and post-Soviet transitions / Robert Levgold -- 9. Combating corruption in traditional societies : Papau New Guinea / Sarah Dix and Emmanuel Pok -- 10. The travails of Nigeria's anti-corruption crusade / Rotimi T. Suberu -- 11. The paradoxes of popular participation in corruption in Nigeria / Daniel Jordan Smith -- 12. Corruption and human rights : exploring the connection / Lucy Koechlin and Magdalena Sepúlveda Carmona -- 13. Leadership alters corrupt behavior / Robert I. Rotberg -- 14. The role of the multi-national corporation in the long war against corruption / Ben W. Heineman, Jr. -- The organization of anti-corruption : getting incentives right / Johann Graff Lambsdorff -- 16. A coalition to combat corruption : TI, EITI, and civil society / Peter Eigen -- 17. Reducing corruption in the health and education sectors / Charles C. Griffin -- 18. Good governance, anti-corruption, and economic development / Jomo Kwame Sundaram.
Contains essays originally prepared for discussion at a series of meetings in 2007 and 2008 held by the Committee on International Security Studies of American Academy of Arts and Sciences, the Program on Intrastate Conflict at the Kennedy School of Government, and the World Peace Foundation -- vii
Includes bibliographical references and index.
Keywords: Political corruption; Transnational crime; Security, International; Nuclear nonproliferation